Numerical Analysis of Effective Permeability of Concrete-Like Material With a Random Three-Phase Mesostructure - Zhang, Shibing; Sun, Zhen; Zhou, Junli; Yang, Bo; Zhang, Jiuchang; Cui, Zhihao (Frontiers in Physics, 2021)
Interfacial transition zone (ITZ) is an important component of the concrete-like material. Accurately simulating the ITZ characteristics of the concrete-like materials is a difficult problem in numerical simulation. This paper proposed a random three-phase mesostructure modeling method using an incorporation of random aggregate generation, Minkowski sum theory and polygon union techniques. It was found that this method can better simulate the mesostructure and ITZ characteristics of concrete-like materials. By using this method, a random three-phase mesostructure model had been built for conducting a finite element analysis to investigate the effective permeability parameters of the concrete. A good agreement between numerical and experiment result indicates the feasibility of this method in concrete-like material analysis.